Analysis of oligomers to assess exposure to microplastics from foods. A perspective - Tsochatzis, Emmanouil D.; Theodoridis, Georgios; Corredig, Milena (Frontiers in Nutrition, 2023)
There is an emerging interest in evaluating the presence of microplastic (MP) and nanoplastic (NP) residues in food. Despite their potential threat to human health, there is still a need for harmonized methods to evaluate and quantify their presence. Incomplete polymerization may occur during the production of plastic. Conversely, oligomers are formed during chemical, mechanical, or enzymatic depolymerization. Oligomers are a few nanometers in size. Recent advances in analytical chemistry have enabled the quantification and identification of these oligomers in various complex biological matrices. Therefore, we propose that the specific nanosized oligomers can be considered markers for the presence of MPs/NPs. This advance may facilitate a broader perspective for the assessment of MPs/NPs exposure, leading to the evaluation of food safety and associated risks to humans.